Sophistication of internet corporate reporting and its impact on corporate performance of listed corporations in Indonesia - Listianto, Gabriel Anto (2018)
In the current digital economy, internet corporate reporting is a competitive necessity for the survival of corporations. Internet corporate reporting facilitates information dissemination to not only the shareholders but also to other stakeholders to reduce information asymmetry. However, not all corporations adopt internet financial reporting. This study aims to contribute to corporate reporting literature by investigating the technological-organizationalenvironmental related factors that affect the adoption of sophisticated internet corporate reporting, and its effect on corporate performance. Moreover, the innovative use of the internet to disseminate financial and non-financial information promotes corporate transparency through more timely and relevant information disclosures to meet the information needs of the corporation’s shareholders and numerous other stakeholders. Primary data were collected from corporations listed on the Indonesia Stock Exchange in 2014 by using questionnaires distributed via mail, e-mail, and web-based survey, while secondary data were collected from corporate annual reports and websites. The structural model based on 74 responses was tested using the partial least square. The empirical findings show that the extent of sophistication of internet corporate reporting is influenced by perceived benefits, ownership concentration, stakeholder orientation, and corporate size. This study carries contributions for the CEOs who should concentrate on the factors relevant to adoption. In addition, this study provides empirical evidence that the sophisticated internet corporate reporting has a positive impact on corporate performance. Furthermore, the relationship between sophisticated internet corporate reporting and corporate performance is mediated by corporate transparency. Consequently, this should motivate the CEOs to adopt a high level of sophisticated internet corporate reporting in order to enhance their corporate transparency and subsequently to enhance corporate performance.